Diatoms in forensic analysis: A practical approach in rats. (July 2015) - Badu, Isaac K; Girela, Eloy; Beltrán, Cristina M; Ruz-Caracuel, Ignacio; Jimena, Ignacio
A diagnosis of drowning is a challenge in legal medicine, as there is generally a lack of pathognomonic findings indicative of drowning. Diatom analysis has been considered very supportive for a diagnosis of drowning, although the test is still controversial for some investigators. We assessed diatoms association with drowning in the peripheral tissues of drowned rats and the effects of the drowning medium on the diatom yield. A modified acid digestion method was optimised for diatom recovery in water and rat tissues. Eighteen adult Wistar rats were employed for the study, subdivided into six groups of three rats. Groups 1, 3 and 5 were drowned in seawater, lake water, or river water respectively, while groups 2, 4 and 6 were controls (immersed after death in seawater, lake water or river water respectively). Water samples were taken from the sea, lake and river in Málaga and Córdoba (Spain) for the purposes of diatomological mapping and drowning of the rats. Diatoms were successfully recovered from all water samples and matched with tissues of the drowned rats. There were significant differences in diatom numbers between control and test samples for all the tissues studied, as well as within test samples. Histological investigations conducted on lung samples obtained from drowned rats provided complementary and valuable information. This study demonstrates the feasibility of the diatom test as a reliable method for the diagnosis of drowning, especially if adequate precautions are taken to avoid contamination, and if interpretation of the analysis is performed in light of other complementary investigations.